2006
DOI: 10.1212/01.wnl.0000219640.59984.a7
|View full text |Cite
|
Sign up to set email alerts
|

Value of 123 I-MIBG radioactivity in the differential diagnosis of DLB from AD

Abstract: Our results indicate that dementia with Lewy bodies results in cardiac sympathetic denervation and that iodine-123 metaiodobenzylguanidine myocardial scintigraphy is a sensitive tool for discriminating dementia with Lewy bodies from Alzheimer disease even in patients without parkinsonism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
155
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(166 citation statements)
references
References 30 publications
(44 reference statements)
9
155
1
1
Order By: Relevance
“…This patient had Braak stage III-IV for neurofibrillary tangles, and no Lewy bodies were found. Based on the literature (Yoshita et al, 2006), an H/M ratio cutoff of 1.68 was used for the classification of patients based on MIBG cardiac scintigraphy. Applying the H/M ratio cutoff of 1.68, 95% (19/20) of the patients with clinically ambiguous diagnoses were correctly classified, with sensitivity and specificity values of 100% (16/16) and 75% (3/4), respectively, as compared with diagnosis at follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This patient had Braak stage III-IV for neurofibrillary tangles, and no Lewy bodies were found. Based on the literature (Yoshita et al, 2006), an H/M ratio cutoff of 1.68 was used for the classification of patients based on MIBG cardiac scintigraphy. Applying the H/M ratio cutoff of 1.68, 95% (19/20) of the patients with clinically ambiguous diagnoses were correctly classified, with sensitivity and specificity values of 100% (16/16) and 75% (3/4), respectively, as compared with diagnosis at follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…The decreased cardiac uptake of MIBG in DLB reflects the postganglionic cardiac sympathetic denervation (Orimo et al, 2005). Promising results have been published, but these studies have been conducted under very strict exclusion criteria (Yoshita et al, 2001, Yoshita et al, 2006, Watanabe et al, 2001, Oide et al, 2003, Hanyu et al, 2006, Wada-Isoe et al, 2007. Indeed, patients with ischemic heart disease, heart failure, thyroid disease, or diabetes mellitus were excluded (Yoshita et al, 2001, Yoshita et al, 2006, Watanabe et al, 2001, Oide et al, 2003.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…57 Cardiac imaging has also been explored and [I-123] myocardial scintigraphy (MIBG) has been shown to be correlate with decreased postganglionic sympathetic innervation with DLB and PD patients with respect to AD patients. 58 There are no definitive biomarkers for DLB, though it has been suggested that a relative increase in CSF tau with decrease in Aβ-42 can distinguish between DLB and PD. 59 Additionally, it has been found that the levels of Aβ-42/Aβ-38 can differentiate between DLB and AD.…”
Section: Studiesmentioning
confidence: 99%